Ethotic Construction in Macron’s Discourse: Towards an Analysis of Enunciative Devices - Lahmar , Maroua; Maiche, Hazar (El Omda in Linguistics and Discourse Analysis, 2023)
In this study, Emmanuel Macron’s last three electoral speeches are analysed using an enunciative approach. The aim is to highlight the mechanisms involved in the process of identity construction. The analysis focuses particularly on markers of the presence of the Other (opponent/citizen) and on their relationship with the discursive image that the candidate seeks to project of himself. To this end, a qualitative analysis was conducted to show, through selected excerpts, how enunciative elements (pronouns and modal markers) contribute to ethotic construction.